Identification of the Conceptual Understanding of the Uniformly Accelerated Rectilinear Motion (GLBB) Material Using PhET Application and the VAK Learning Model among Junior High School Students - Eka Nurlita Anggraeni; Inggrid Ayu Amala; Iwan Wicaksono; Aris Singgih Budiarso (Universitas Negeri Yogyakarta, 2018)
Junior high school students find it difficult to understand the materials and the concepts in science learning because the teaching method that is too monotonous. It is the lecturing method where students are less involved in learning activities, and this has led to the decline in students’ learning outcomes in science learning. The use of media and learning models play an important role. The popular media in learning are modern media, in this case PhET application. This application can give the impression of a direct experiment among students without ignoring technological developments where IT is needed by students. This study aims to identify students' conceptions on concepts. The type of this research was a library research. This study used the VAK learning model (Visual, Auditory, and Kinesthetic). In the VAK learning model, the teacher can combine three teaching-learning styles. 1) The teacher will prioritize the demonstration or the media by showing the teaching tools directly to the students and describing them on the board. 2) In learning by listening, the teacher must be able to explain clearly and in detail so that the students can understand the material presented. 3) In learning practice, after the students listen and learn through physical activity and direct involvement, they must conduct a direct experiment to gain deeper understanding of the materials. In this library research, the researchers searched for some references related to the research.